The Roadmap for a Prospective US-ASEAN FTA: Legal and Geopolitical Considerations - HSIEH, Pasha L. (Institutional Knowledge at Singapore Management University, 2012)
This article examines the legal framework governing economic relations between the United States and the Association of Southeast Asian Nations (ASEAN) and outlines a roadmap for a US-ASEAN Free Trade Agreement (FTA). Notwithstanding ASEAN’s emerging centrality in Asian regionalism, America remains the only Pacific power that has not concluded any form of FTA with ASEAN.This article explains that limited progress in Washington’s efforts stemmed from the domestic politics of the US Trade and Investment Framework Agreement (TIFA) approach and the Myanmar dilemma. It further analyses the challenges that the Trans-Pacific Partnership (TPP) Agreement negotiations have encountered and contends that the TPP cannot be a substitute for a US-ASEAN FTA. Finally, a ‘Plan B’ roadmap to reinvigorate US-ASEAN trade ties is proposed.This roadmap calls for an enhanced TIFA that incorporates the building block features of ASEAN’s framework agreements, thereby laying a solid yet gradual foundation for an FTA. This research therefore provides a valuable study of a region-based FTA under the multilateral trading system.